N-methyl-d-aspartate receptor blockade during development lowers long-term potentiation threshold without affecting dynamic range of CA3-CA1 synapses - Savić, Nataša (The National Academy of Sciences, 2003)
During development, excitatory synapses in the CA1 region of the hippocampus undergo activity-dependent and N-methyl-d-aspartate (NMDA) receptor-dependent long-lasting changes in synaptic efficacy. These bidirectional changes occur between limits that determine the dynamic range within which synapses operate. It is unknown whether the dynamic range itself is also activity-dependent and NMDA receptor-dependent. Here, we show that chronic blockade of NMDA receptors in hippocampal slice cultures during early postnatal development does not affect the dynamic range but results in a lower threshold for the induction of long-term potentiation. Thus, the dynamic range of CA3-CA1 synapses, unlike long-term potentiation threshold, is NMDA receptor-independent, thereby providing functional stability to the hippocampal network during development.